A trade‐off between antipredatory behavior and pairing competition produced by male‑male tandem running in three Reticulitermes species. (11th November 2014) - Li, Gang‐Hua; Liu, Long; Lei, Chao‐Liang; Huang, Qiu‐Ying
Abstract Due to the omnipresent risk of predation, termites have evolved many antipredatory behaviors. The two related species Reticulitermes speratus and R. chinensis have been demonstrated to use homosexual tandem running to decrease individual predation risk after shedding their wings. In this study, we tested risk of predation in the termite R. flaviceps, which is distantly related to the above two species. We determined that homosexual tandem running also led to low individual predation risk in dealates of R. flaviceps. Moreover, by combining a predation model with a competition model, we observed a typical trade‐off phenomenon between antipredatory behavior and pairing competition produced by male‑male tandem running in the above three Reticulitermes species. Our results indicated that male‑male tandem running could effectively protect disadvantaged individuals from being caught, but disadvantaged individuals would be easily eliminated in pairing competition after male‑male tandem running, suggesting that male‑male tandem running can promote population evolution in termites by repeatedly removing the relatively inferior male individuals.